An Information Cardiac Platform to Support Healthcare - Georgieva-Tsaneva, Galya; Gospodinova, Evgeniya; Bogdanova, Galina; Dimitrova, Diana (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The article presents a software information platform for storing, processing, researching, and protecting cardiology information obtained during the study of patients with various cardiovascular diseases and a healthy control group. The information platform contains non-confidential data about the research subjects, which is freely available; as well as a confidential part; cardiological data, containing information about the biomedical tests carried out; as well as the parametric and graphical results of the mathematical analyzes obtained based on the registered cardiac data. The created integrated information platform can be used by cardiology specialists to evaluate the results of cardiac examinations and assist cardiologists in making a correct diagnosis and prescribing effective treatment. The platform is a tool with a user-friendly interface and can be useful for cardiac data researchers as well.